33. INITIAL RESULTS OF 10 CASES OF LAPAROSCOPIC SURGERY TRANSITONOLOGY TO RECOVER KIDNEYS FOR TRANSPLANTATION FROM LIVING DONORS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the results of transperitoneal laparoscopic surgery for transplanted kidneys on living donors at Thong Nhat Hospital.Subjects and methods: Prospective studies. There are 10 cases of living kidney donors undergoing laparoscopic peritoneal surgery to remove kidneys for transplantation at Thong Nhat Hospital from May 15, 2022 to March 7, 2024. The kidney donor voluntarily donates 1 kidney to a person with end-stage chronic kidney disease, meeting the criteria for selecting a donor-recipient pair in accordance with the regulations of the Viet Nam Ministry of Health. All 10 cases were performed by transperitoneal laparoscopic surgery for kidney removal.Results: All 10 cases were taken from the left kidney, average age 42.5 ± 8.55 years, male/female ratio: 6/4 cases, same-blood donor: 9/10 cases, non-blood 1/10 cases, surgery time: 105 ± 20.15 (90 – 150 minutes), duration of thermal anemia: 3.9 ± 0.99 (3 – 5 minutes), Hospital stay 6.50 ± 0.70 days (6 – 8 days).Conclusion: Through 10 cases of laparoscopic kidney removal surgery for transplantation from living kidney donors with support from experts from Cho Ray Hospital, it has been shown that transperitoneal laparoscopic surgery for kidney removal is a safe and effective surgery with a short hospital stay, gentle post-surgery.
Keywords: Kidney transplant; living donor nephrectomy; transperitoneal laparoscopic